Clinical Case of Heiner Syndrome - V.A. Klimenko; A.M. Ascheulov; N.T. Sindeyeva (Zaslavsky O.Yu., 2014)
The article presents a clinical observation of the child with a rare nosological entity - Heiner syndrome. Syndrome is characterized by a primary lesion of the lungs, in the pathogenesis the leading factor is hypersensitivity to cow's milk proteins.